Frequency of homologous blood transfusion in patients undergoing cleft lip and palate surgery - Wasiu L. Adeyemo; Mobolanle O. Ogunlewe; Ibironke Desalu; Akinola L. Ladeinde; Titilope A. Adeyemo; Bolaji O. Mofikoya; Olakunle O. Hassan; Alani S. Akanmu (Indian Journal of Plastic Surgery)
Aim: The study aims to determine the frequency of homologous blood transfusion in patientsundergoing cleft lip and palate surgery at the Lagos University Teaching Hospital, Nigeria. Setting and Design: A prospective study of transfusion rate in cleft surgery conducted at the Lagos University Teaching Hospital, Nigeria. Material and Methods: One hundred consecutive patients who required cleft lip and palate surgery were recruited into the study. Data collected included age, sex and weight of patients, type of cleft defects, type of surgery done, preoperative haematocrit, duration of surgery, amount of blood loss during surgery, the number of units of blood cross-matched and those used. Each patient was made to donate a unit of homologous blood prior to surgery. Results: There were 52 females and 48 males with a mean age of 64.4 ± 101.1 months (range, 3-420 months). The most common cleft defect was isolated cleft palate (45%) followed by unilateral cleft lip (28%). Cleft palate repair was the most common procedure (45%) followed by unilateral cleft lip repair (41%). The mean estimated blood loss was 95.8 ± 144.9 ml (range, 2-800ml). Ten (10%) patients (CL=2; CP=5, BCL=1; CLP=2) were transfused but only two of these were deemed appropriate based on percentage blood volume loss. The mean blood transfused was 131.5 ± 135.4ml (range, 35-500ml). Six (60%) of those transfused had a preoperative PCV of < 30%. Only 4.9% of patients who had unilateral cleft lip surgery were transfused as compared with 50% for CLP surgery, 11% for CP surgery, and 10% for bilateral cleft lip surgery. Conclusions: The frequency of blood transfusion in cleft lip and palate surgery was 10% with a cross-match: transfusion ratio of 10 and transfusion index of 0.1. A “type and screen” policy is advocated for cleft lip and palate surgery.